2014
DOI: 10.1007/s10459-013-9480-6
|View full text |Cite
|
Sign up to set email alerts
|

Validating MMI scores: are we measuring multiple attributes?

Abstract: The multiple mini-interview (MMI) used in health professional schools' admission processes is reported to assess multiple non-cognitive constructs such as ethical reasoning, oral communication, or problem evaluation. Though validation studies have been performed with total MMI scores, there is a paucity of information regarding how well MMI scores differentiate the constructs being measured, the relationship between MMI scores (construct or total) and personality characteristics, and how well MMI scores (const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 29 publications
3
47
3
Order By: Relevance
“…Within these analyses of multiple correlations, Kulasegaram et al (2010) and Griffin & Wilson (2012) applied Bonferroni corrections, whereas Jerant et al (2012) and Oliver et al (2014) did not appear to, so the associations reported in the latter two studies are more likely to have suffered type 1 errors. Yen et al (2011) reported no correlation between a validated self-report measure of emotional intelligence, defined as 'a type of social intelligence that involves the ability to monitor one's own thinking and actions' (Salovey & Mayer 1990), and total MMI score for 196 applicants for admission to the health sciences programme at the Michener Institute for Applied Health Sciences.…”
Section: P<0mentioning
confidence: 97%
See 2 more Smart Citations
“…Within these analyses of multiple correlations, Kulasegaram et al (2010) and Griffin & Wilson (2012) applied Bonferroni corrections, whereas Jerant et al (2012) and Oliver et al (2014) did not appear to, so the associations reported in the latter two studies are more likely to have suffered type 1 errors. Yen et al (2011) reported no correlation between a validated self-report measure of emotional intelligence, defined as 'a type of social intelligence that involves the ability to monitor one's own thinking and actions' (Salovey & Mayer 1990), and total MMI score for 196 applicants for admission to the health sciences programme at the Michener Institute for Applied Health Sciences.…”
Section: P<0mentioning
confidence: 97%
“…Oliver et al (2014) investigated the associations between MMI and extroversion and emotionality, and reported extroversion was associated with higher MMI score (r=0.22, P<0.05) but emotionality was not (r=-0.01, n/s).…”
Section: P<0mentioning
confidence: 99%
See 1 more Smart Citation
“…19–21 According to the literature, the categories selected in this case—professionalism, critical thinking, and communication—are appropriate for the PT profession. 22–28 The findings of this study confirmed that the CBS categories are valid; however, they are also overlapping and interrelated, especially communication and professionalism, and this question merits further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Shouldn't there be convergent and discriminant evidence demonstrating the utility of the attributes being measured? Indeed Oliver et al (Oliver et al 2014) tried to ''draw a line in the sand'' and suggest that if we are measuring multiple attributes using an MMI, then we should attempt to show some evidence of differential prediction form the various sub-components. While some evidence of convergent and discriminant validity was provided, the correlation between communication and problem evaluation was large (.87).…”
mentioning
confidence: 99%